2004
DOI: 10.1038/nm1055
|View full text |Cite
|
Sign up to set email alerts
|

PrPSc accumulation in myocytes from sheep incubating natural scrapie

Abstract: Because variant Creutzfeldt-Jakob disease (vCJD) in humans probably results from consumption of products contaminated with tissue from animals with bovine spongiform encephalopathy, whether infectious prion protein is present in ruminant muscles is a crucial question. Here we show that experimentally and naturally scrapie-affected sheep accumulate the prion protein PrP(Sc) in a myocyte subset. In naturally infected sheep, PrP(Sc) is detectable in muscle several months before clinical disease onset. The relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
88
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 11 publications
14
88
1
1
Order By: Relevance
“…This neuroinvasion apparently occurs via the enteric nervous system and its nerve fibres (Andreoletti et al, 2000;van Keulen et al, 2000), although haematogenous spread has also been proposed as a contributory/alternative route . From there the agent redistributes (centrifugally) to the peripheral nervous system and skeletal muscle (Andreoletti et al, 2004). In blood, infectivity and PrP Sc can be detected as early as at three months of age, and persist throughout the incubation period (Lacroux et al, 2012).…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…This neuroinvasion apparently occurs via the enteric nervous system and its nerve fibres (Andreoletti et al, 2000;van Keulen et al, 2000), although haematogenous spread has also been proposed as a contributory/alternative route . From there the agent redistributes (centrifugally) to the peripheral nervous system and skeletal muscle (Andreoletti et al, 2004). In blood, infectivity and PrP Sc can be detected as early as at three months of age, and persist throughout the incubation period (Lacroux et al, 2012).…”
Section: Disease Pathogenesismentioning
confidence: 99%
“…To achieve this, we used a genetically modified mouse line that overexpresses the sheep VRQ allele and is considered to be highly effective in the detection of scrapie infectivity, demonstrated by the short incubation period observed after inoculation of brain homogenates from infected VRQ/VRQ or VRQ/ARQ sheep from the same flock (Telling et al 1995, Vilotte et al 2001. The tg338 mouse line has been proved to be able to detect infectivity in a tissue with less than 1/5000 brain infectivity, which is equivalent to sensitivity within the picogram range of Prp sc per milligram of tissue (Andreoletti et al 2004). Our results demonstrated that the transmission of scrapie did not occur with semen from infected rams at any point during scrapie incubation, even with a highly infected animal such as the oldest VRQ/VRQ ram that was sampled at the clinical stage and when spermatozoa and seminal plasma (and also cells and organelles that can be found within this fluid , Sutovsky et al 2007) contain undetectable levels of infectivity.…”
Section: Prpmentioning
confidence: 99%
“…28 This heterogeneity makes estimating the levels of PrP res in muscle difficult. However, in the positive muscle samples the signals obtained for 50 mg of muscle tissue were equivalent to 0.1 mg of vCJD brain (cerebral cortex) used as a positive control (Figures 1 to 3).…”
Section: Heterogeneous Distribution Of Prp Res In Skeletal Musclementioning
confidence: 99%